Upper Limb Muscles Activity during Punches in Virtual Reality Exergame on Standing and Sitting Position - Putra, Bayu Aji Mayogya; Masduchi, Reni Hendrarati; Tinduh, Damayanti; Pawana, I Putu Alit (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: Physical activity (PA) provides various health benefits. Unfortunately, individuals with disabilities may experience health problems and greater obstacles to PA participation. Boxing exergame (EXG) based on virtual reality (VR) can be an alternative option to increase physical activity level because it is fun, relatively affordable and accessible. Punching in boxing requires complex movements, wherein the lower limbs are contributor for effective punches. An understanding of muscles activity is important to uncover the potential benefits of VR EXG.Aim: To evaluate the differences in upper limb muscles activity of the dominant side in standing compared to sitting position during punches.Material and methods: This was a cross-sectional study involving 15 healthy adult men. Surface electromyography examinations was performed on four upper limb muscles of the dominant side (upper trapezius, anterior deltoid, biceps, triceps) when delivering straight, hook and uppercut punches while playing VR EXG "Fitness Boxing" Nintendo Switchâ„¢ in standing and sitting position.Results: Fifteen healthy men (age 31.87±3.14 years old, BMI 23.77±2.47 kg.m-2) were participated in this study. No significant difference found in the percentage of maximum voluntary isometric contraction (%MVIC) values of the upper trapezius, anterior deltoid, biceps and triceps muscles of the dominant sides when the subjects delivered straight, hook and uppercut punches (p>0.05), except for upper trapezius muscle during uppercut punch in standing compared to sitting position (p=0.041).Conclusion: The VR EXG "Fitness Boxing" Nintendo Switchâ„¢ can be done in a standing or sitting position to get similar effect on the upper limb muscles.